Another Look at the Predictive Power of the Yield Spread: New Evidence - Lee , Unro (Journal of Accounting and Finance, 2021)
The yield spread, i.e. the spread between the long-term Treasury yield and the short-term yield, has long been regarded as a good predictor of future economic activity. There is also a plethora of research that posits a strong relationship between real stock returns and future economic activity. This study investigates the dynamic relationship among the yield spread, real stock returns and real economic activity for the United States. Four alternative measures of the yield spread are employed to determine the sensitivity of the empirical results with respect to the choice of the yield spread. It is found that the yield spread measured as the gap between the 10-year and the 3-month Treasury yields is a good predictor of the real economic activity. Furthermore, the yield spread with the federal funds rate as the proxy for the short-term interest rate is a good prognosticator of future real stock returns.